Evaluation of LD50 Value of the Phytopesticide Piperidine on the Adult Male Insect Odontopus varicornis (Heteroptera: Pyrrhocoridae) - Mohan, T. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The piperidine structural modification is present in numerous natural alkaloids. These include piperine, which gives black pepper and fire ant venom. The present work has been undertaken to evaluate the sub lethal concentration (LD50) value of piperidine on Odontopus varicornis. The changes in the mortality of Odontopus varicornis was observed at various exposure period for 24, 48, 72 and 96 hours and its sublethal concentration was found to be about 0.15% for 48 hours. When the insects were injected with sublethal concentration 0.15% for 48 hours, led to 50% mortality of the test insects.